New Media’s Presentness and the Question of History: Craigie Horsfield’s Broadway Installation - Ross, Christine (Cinémas)

(untitled) (Cinémas, 2006)
AbstractIn the last three decades, media art (in both its analogue and digital forms) has been consistently defended in its alleged ability to, in the words of art critic Jean-Christophe Royoux, to “give concrete form to what, as a rule, vanishes from cinematographic time: the present.” Questions emerge, however, as to what exactly constitutes the present and, more importantly—in works that privilege presentness—how can the past and the future can still be productive categories of time? Indeed, such a privileging might be more problematic than initially thought. This, at least, is what comes out from a study by historian François Hartog who maintains that the prevailing regime of historicity today is not liberating access to the present but presentism: the turning of the present into an absolute value, whose absoluteness means a real disconnection from the past and the future. In such a regime, it is the possibility of history which is threatened with disappearance. This article seeks to examine the apparent incompatibility between new media art’s presentist inclination and the sense of history. To investigate this tension, it is imperative to look at artworks that address one of the main challenges of a culture obsessed with the present—the setting of the conditions of the possibility of history. I propose that Craigie Horsfield’s work is an original contribution to this line of investigation. Special attention is given here to the three main aesthetic strategies constitutive of the video installation Broadway (2006): the solicitation of attention, the temporalization of the horizon line and the convergence of two viewing positions—those of the spectator and the witness.